2020
DOI: 10.31234/osf.io/9yqs8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effectiveness of moral messages on public health behavioral intentions during the COVID-19 pandemic

Abstract: With the COVID-19 pandemic threatening millions of lives, changing our behaviors to prevent the spread of the disease is a moral imperative. Here, we investigated the persuasiveness of messages inspired by three major moral traditions. A sample of US participants representative for age, sex and race/ethnicity (N=1032) viewed messages from either a leader or citizen containing deontological, virtue-based, utilitarian, or non-moral justifications for adopting social distancing behaviors during the COVID-19 pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
271
9
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(317 citation statements)
references
References 16 publications
25
271
9
3
Order By: Relevance
“…In Table 5 we provide all items used to assess compliance with public health behaviors and social identity affirmation in isolation. Everett et al, 2020; 1 = "Not at all" to 5 = "Always" scale)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 5 we provide all items used to assess compliance with public health behaviors and social identity affirmation in isolation. Everett et al, 2020; 1 = "Not at all" to 5 = "Always" scale)…”
Section: Methodsmentioning
confidence: 99%
“…In mere months, this novel coronavirus unleashed a global pandemic of COVID-19. The spread of the coronavirus is reshaping social life, and social psychology is at the forefront of studying these changes (e.g., Everett, Colombatto, Chituc, Brady, & Crockett, 2020;Van Bavel et al, 2020). Essential to this research is understanding-and measuring (Flake, Pek, & Hehman, 2017)-how people perceive the threat of the virus.…”
Section: Measuring Realistic and Symbolic Threats Of Covid-19 And Thementioning
confidence: 99%
“…Second, while our regression models have utility for informing how public health behavioral compliance can be predicted from an individual differences perspective, it lacks the identification and understanding of any potential barriers to bringing about said change. It is here where experimental studies emerging about the response to COVID-19 (e.g., Everett et al 2020) can be supplemented by correlational data such as ours in order to bring about a more comprehensive view of public health compliance and the effectiveness of government messaging. Finally, we are mindful that data has been collected at a single time point within an unprecedented period of time.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…This research examines how to encourage prosocial and virus-mitigating responses (e.g., social distancing, or the non-hoarding of food and household supplies, and good hand hygiene). For example, Everett et al (2020) reported how communicating advice using deontological moral advice (i.e., in ways that invoke a sense of civic duty) has a modest effect on increasing a propensity to engage in behaviors that enhance a delay in the transmission of the virus (e.g., hand washing, avoiding large gatherings, and sharing government advice on preventing the spread of . This sense of duty taps into themes of interpersonal empathy, with Oosterhoff and Palmer (2020) findings that American adolescents who demonstrated higher levels of subjective self-interest were more likely to hoard supplies and less likely to refrain from nonessential social interactions.…”
mentioning
confidence: 99%
“…After the COVID-19 pandemic, world health organization (WHO) has recommended that individuals wash hands more frequently and at least for 20 seconds to ensure bacterial and virus removal from the skin [8,9]. It has been shown that the lipid outer layer of SARS-CoV-2 disrupts after long enough contact time with anionic surfactants [10].…”
Section: Introductionmentioning
confidence: 99%